Implementasi IoT pada Kotak Donasi dengan Sensor TCS3200 untuk Deteksi Uang Kertas Menggunakan Firebase dan Bot Telegram - Anggraini, Nenny; Shaeku, Muhammad Akhil (Jurnal Informatika Universitas Pamulang, 2024)
Mosques are the center of Muslim spiritual and community life, thus requiring effective financial management. This research aims to develop a smart donation box based on Internet of Things (IoT) technology to improve efficiency and transparency in donation management. This research methodology uses a prototyping method consisting of the stages of Communication, Quick Planning, Quick Modeling, Construction, and Evaluation, which are designed to quickly produce functional prototypes. The results showed that the smart donation box was able to detect and count paper money with an optimal success rate of 85% at a sensor distance of 1 cm. However, the detection rate decreased to 57% at a distance of 0.5cm and 42% at a distance of 1.5cm, indicating that the position of the sensor significantly affects performance. The system enables real-time financial monitoring through the Telegram app, significantly increasing the transparency of mosque financial management.